Introduction to “Advances in Longitudinal HCI Research” - Karapanos, Evangelos; Gerken, Jens; Kjeldskov, Jesper; Skov, Mikael B. (My University, 2021)
Aimed as an educational resource for graduate students and researchers in HCI, this book brings together a collection of chapters, addressing theoretical and methodological considerations, and presenting case studies of longitudinal HCI research. In this short introduction to the book, we reflect on the need for longitudinal studies in human–computer interaction research, we define what is and what is not longitudinal research and outline the selected contributions.
Keywords: Longitudinal research; Empirical studies